Emerging insights into wine polysaccharides: Mechanisms, evolutions and applications in wine flavor management - Zhenyue Yang; Linna Song; Yujie Hao; Nannan Liu; Ziyu Wei; Xiaxia Hou; Yu Gao; Wen Ma (Trends in Food Science & Technology, 2026)

Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Nonlinear and spatially heterogeneous carbon effects of three-dimensional urban expansion in China - Zilin Deng; Ziyan Luo; Linna Li; Yueting Ma; Yaqun Liu (Environmental Impact Assessment Review, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Contrasting effects of partial organic substitution and its inoculation with phosphate-solubilizing bacteria on stoichiometric imbalances and phosphorus fractions accumulation after six-year application in a rice paddy - Xinxin You; Wenyi Xu; Linna Du; Sheng Wang; Yan Zhou; Xiaomin Ma; Hua Qin; Junhui Chen (Soil and Tillage Research, 2026)

Context-dependent reshaping of rhizosphere microbial communities by intercropping systems: A systematic analysis of 32 crop combinations - Feixue Li; Linna Ma; Jingyu Li; Chen Ye; Xinyue Mei; Siji Zhao; Yiwen Li; Yixiang Liu; Huichuan Huang; Xiang Li (Rhizosphere, 2026)

Corrigendum to “Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification”. [J. Hydrol. 662 (2025) 133818] - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2026)

Freeze–thaw cycling effects on Pb and Cd immobilization by green waste compost in contaminated soil - Jie Ma; Chenchen Wang; Linna Suo; Yuanxin Liu; Xiangyang Sun (Journal of Soils and Sediments, 2026)

Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2025)

Petrogenesis of the Niancaowan mafic-ultramafic intrusion: Decoding magmatic evolution in the cu Ni Metallogenic Province of the Bayan obo rift zone - Linna LI; Jiangang JIAO; Yunfei MA (Geochemistry, 2025)

Olive oil additive enhances hyphal growth and triterpenes accumulation in submerged fermentation of Grifola frondosa - Qiaoyu Wang; Chenmeng Wan; Ke'er Xiao; Zijian Tong; Ziteng Zhao; Xinyu Meng; Mukaddas Sai; Yajie Bao; Lili Guan; Hongxia Ma; Linna Du (Fungal Biology, 2025)

The role of circSUCLG2 in mediating inflammatory response and bone remodeling imbalance in diabetic osteoporosis - RenZhou Wang; LinNa Ma (Molecular & Cellular Toxicology, 2025)

Structural, functional and antioxidant characteristics of enzymatic hydrolysates from Cantharellus cibarius protein - Yunxiang Que; Xingrui Liu; Pinyao Liu; Wenqi Liu; Haipeng Zhang; Chengguang He; Huining Dai; Linna Du; Hongxia Ma; Lili Guan (Food Chemistry, 2025)

Compartment-specific core microbiomes and functions in rice - Linna Ma; Yusha Bai; Xiang Li; Jingyu Li; Feixue Li; Yan Yue; Yingguang Li; Jingwen Guo; Chen Ye; Xinyue Mei; Fei Du; Yixiang Liu; et al. (Plant and Soil, 2025)

The pass-through mechanism for carbon emission cost under ETS with different accounting principles: a focus on construction supply chains - Shanshan Huang; Bing Wang; Linna Geng; Jiajun Ma (Environment, Development and Sustainability, 2025)

Soil microbial community and chemical properties response to blueberry–soybean intercropping system - Linna Ma; Xiang Li; Zhiping Zhang; Ting Zhang; Haibin Duan; Huichuan Huang; Yixiang Liu; Shusheng Zhu; Youyong Zhu; Yingbin Li (Plant and Soil, 2025)

Niche-specific evolution and gene exchange of Salmonella in retail pork and chicken - Huanjing Sheng; Linna Zhao; Jia Suo; Qiuping Yang; Chenyang Cao; Jia Chen; Guangqing Cui; Yiling Fan; Yi Ma; Shengnan Huo; Xin Wu; Tao Yang; et al. (Food Research International, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Biotic and abiotic drivers of ecosystem multifunctionality: Evidence from the semi-arid grasslands of northern China - Congwen Wang; Wanying Yu; Linna Ma; Xuehua Ye; Enkhmaa Erdenebileg; Renzhong Wang; Zhenying Huang; Tuvshintogtokh Indree; Guofang Liu (Science of The Total Environment, 2023)

Remote Estimation of the Chlorophyll-a Concentration in Lake Dianshan, China Using High-Spatial-Resolution Satellite Imagery - Xiaoman Lu; Chunyan Situ; Jiajia Wang; Liguo Zhou; Weichun Ma; Linna Li (Journal of the Indian Society of Remote Sensing, 2022)

Plant diversity has stronger linkage with soil fungal diversity than with bacterial diversity across grasslands of northern China - Congwen Wang; Linna Ma; Xiaoan Zuo; Xuehua Ye; Renzhong Wang; Zhenying Huang; Guofang Liu; Johannes H. C. Cornelissen (Global Ecology and Biogeography, 2022)
Aim The interactions between plants and soil microbes play crucial roles in modulating the function and stability of terrestrial ecosystems. However, the relationships between plant and soil microbial diversity for different taxa have remained been elusive. Location Northern China. Major taxa Plant and soil microbes of grassland ecosystems. Time period 2018 and 2019. Methods We conducted a transect survey across grasslands to measure plant diversity, plant traits, and soil microbial diversity. High throughput sequencing was used to assess soil microbial diversity for bacterial 16S ribosomal RNA (16S) and fungal internal transcribed spacer (ITS) regions on an Illumina MiSeq. The random forest algorithm was used to determine the important spatial and environmental variables in predicting plant and microbial diversity, and structural equation modelling was used to examine the direct and indirect effects of climatic and edaphic variables on plant and microbial diversity. Results Plant diversity was positively correlated with the diversity of soil fungi, particularly for predicted arbuscular mycorrhizal fungi (AMF) and saprotrophic fungi, and they were positively related to soil nutrients and texture. However, the correlation between plant and bacterial diversity varied by phyla and functional guilds, resulting in decoupling between plant and soil bacterial diversity. Community weighted mean leaf C:N ratio indirectly decreased soil fungal diversity through a negative relationship with soil total nitrogen. Soil bacterial and fungal diversity increased with increasing functional richness of specific leaf area and stem density, respectively. Main conclusions These findings have contributed to unravelling the direct and indirect linkages between plant and soil fungal diversity, highlighting particularly strong linkages between plant diversity and predicted AMF and saprotrophic fungi diversity. However, we failed to detect an overall linkage between plant and soil bacterial diversity. Still, our findings suggest that integrating soil fungi into the framework of plant diversity conservation is conducive to biodiversity restoration in degraded grassland ecosystems.

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

Comparative analysis of four semi-analytical models for estimating chlorophyll- a concentration in case-2 waters using field hyperspectral reflectance - Xiaoman Lu; Chunyan Situ; Weichun Ma; Xiaoyan Dai; Cheng He; Linna Li; Liguo Zhou (International Journal of Remote Sensing, 2020)

Synthetic FXR Agonist GW4064 Prevents Diet-Induced Hepatic Steatosis and Insulin Resistance - Yongjie Ma; Yixian Huang; Linna Yan; Mingming Gao; Dexi Liu (Pharmaceutical Research, 2013)